Plasmon-Enhanced Surface Photovoltage of ZnO/Ag Nanogratings - Gwon, Minji (Sci Rep, 2015)
We investigated the surface photovoltage (SPV) behaviors of ZnO/Ag one-dimensional (1D) nanogratings using Kelvin probe force microscopy (KPFM). The grating structure could couple surface plasmon polaritons (SPPs) with photons, giving rise to strong light confinement at the ZnO/Ag interface. The larger field produced more photo-excited carriers and increased the SPV. SPP excitation influenced the spatial distribution of the photo-excited carriers and their recombination processes. As a result, the SPV relaxation time clearly depended on the wavelength and polarization of the incident light. All of these results suggested that SPV measurement using KPFM should be very useful for studying the plasmonic effects in nanoscale metal/semiconductor hybrid structures.